2021
DOI: 10.1039/d1nj04159b
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning nanofiber technology: a multifaceted paradigm in biomedical applications

Abstract: This review focuses on the process of preparation of nanofibers via Es, the design and setup of the instrument, critical parameter optimization, preferable polymers, solvents, characterization techniques, and recent development and biomedical applications of nanofibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 175 publications
0
31
0
Order By: Relevance
“…5,6 The wastewater management systems frequently fail in the effective elimination of drug-like contaminants, the removal of which is currently one of the important environmental concerns. 7,8 The drugs present in waterbodies even at low concentrations may negatively affect the life of aquatic organisms and animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The wastewater management systems frequently fail in the effective elimination of drug-like contaminants, the removal of which is currently one of the important environmental concerns. 7,8 The drugs present in waterbodies even at low concentrations may negatively affect the life of aquatic organisms and animals.…”
Section: Introductionmentioning
confidence: 99%
“…Although diverse approaches including ozonation, 4,11 oxidation, 12,13 reduction, photolysis, and gamma-ray irradiation have been utilized for MNZ removal, many of them still have limitations in terms of efficacy and cost. 4 Adsorption is an environmentally benign method with low adverse impacts on the environment, 7 as it can efficiently be applied to eliminate contaminants (including pharmaceuticals) from water and gas mixtures. 14,15 This versatile and cost-effective method is usually characterized by low energy consumption with a limited use or production of harmful products and auxiliary materials.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 The electrospun nanomaterials possess many advantages, including high porosity, high surface area to volume ratio, good thermal stability, good connectivity, tunable wettability, fine flexibility, easy fabrication and functionalization, and therefore, more and more researchers have paid attention to their fabrication and applications for sensing, air filtration, water purification, heterogeneous catalysis, environmental protection, energy harvesting/conversion/storage, drug delivery/release, biomedical engineering, and so on. 1–8 At present, some E-spun photocatalytic materials (E-spun PCMs) such as electrospun Bi modified BiVO 4 , 8 polyvinylpyrrolidone/poly(vinylidene fluoride)/TiO 2 , 9 TiO 2 /g-C 3 N 4 , 10 graphene oxide/MIL-101(Fe)/poly(acrylonitrile- co -maleic acid), 11 pea-like TiO 2 @GO, 12 Pd decorated polydopamine-SiO 2 /PVA, 13 β-FeOOH/TiO 2 , 14 and polydopamine-coated tungsten oxide@poly(vinylidene fluoride- co -hexafluoropropylene) 15 have been developed and applied in the removal of organic pollutants from environmental water samples. These reported results demonstrated that the E-spun PCMs were efficient, stable, and easily recoverable photocatalysts for pollutant degradation, 9–15 and thus more novel E-spun PCMs are desired for pollutant removal.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 At present, electrospun membranes have been applied for membrane separation, 3 brine treatment, [4][5][6] air filtration, 7 and various biomedical fields. 8 Owing to their higher porous structure, and larger surface area, electrospun membranes are suitable for drug loading and potentially facilitate the release of drug molecules from the matrix, which is a high application hotspot, 9,10 in which organicinorganic composite membranes are more attractive since their flexibility, higher mechanical strength, and easier modification. 11 With the request for a more comfortable life, intelligent drug release systems are needed for better therapeutic efficacy and reduced side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic spinning has become one of the potential technologies for producing membranes due to its simple procedure and ultrafine control of the average fiber diameters from submicron to nanometer 1,2 . At present, electrospun membranes have been applied for membrane separation, 3 brine treatment, 4–6 air filtration, 7 and various biomedical fields 8 . Owing to their higher porous structure, and larger surface area, electrospun membranes are suitable for drug loading and potentially facilitate the release of drug molecules from the matrix, which is a high application hotspot, 9,10 in which organic–inorganic composite membranes are more attractive since their flexibility, higher mechanical strength, and easier modification 11 …”
Section: Introductionmentioning
confidence: 99%